Human Immunocompetent Model of Neuroendocrine Liver Metastases Recapitulates Patient-Specific Tumour Microenvironment - Doornebal, Ewald Jan; Harris, Nicola; Riva, Antonio; Jagatia, Ravi; Pizanias, Michail; Prachalias, Andreas; Menon, Krishna; Preziosi, Melissa; Zamalloa, Ane; Miquel, Rosa; Zen, Yoh; Orford, Michael Robert; et al. (Frontiers in Endocrinology, 2022)
Neuroendocrine liver metastases (LM-NEN) develop in a considerable proportion of patients with gastroenteropancreatic neuroendocrine neoplasms. There is a paucity of experimental models that accurately recapitulate this complex metastatic human liver microenvironment precluding scientific and clinical advancements. Here, we describe the development of a novel personalised immunocompetent precision cut tumour slice (PCTS) model for LM-NEN using resected human liver tissue. The histological assessment throughout the culture demonstrated that slices maintain viability for at least 7 days and retain the cellular heterogeneity of the original tumour. Essential clinical features, such as patient-specific histoarchitecture, tumour grade, neuroendocrine differentiation and metabolic capacity, are preserved in the slices. The PCTS also replicate the tumor-specific immunological profile as shown by the innate and adaptive immunity markers analysis. Furthermore, the study of soluble immune checkpoint receptors in the culture supernatants proves that these immunomodulators are actively produced by LM-NEN and suggests that this process is epithelium-dependent. This model can be employed to investigate these pathways and provides a powerful platform for mechanistic, immunological and pre-clinical studies.